Pengaruh Media Kecambah Pasir Tsunami dan Kedalaman Tanam Terhadap Vigor Benih Jagung Manis (Zea mays saccharata STURT.) Varietas Manise-1 - Syafruddin Syafruddin (Jurnal Agrista, 2006)
Effect of Germination Medium From Sands of Tsunami and Deep Planting on the Vigor of Sweet Corn (Zea mays saccharata STURT.) Variety Manise-1ABSTRACT. The research was conducted in Seed Science and Technology Laboratory, Agriculture Faculty Syiah Kuala University from February until June 2005. The purpose of this research is to explain the effect of germination medium from sands of tsunami, deep planting and interaction between these factor on the vigor of sweet corn seed var. Manise-I. Factorial type of Completely Randomized Design with three replications was used in the experiment. The factor germination medium consist at three levels; river sand, sands of tsunami sand, washed tsunami sand; whereas deep planting factor consist of 2, 3, and 4 cm. The research result show that germination medium from sands of tsunami had high significant different on all parameters which consist of growth potential, germination ability, growth velocity, growth sincronization, and seedling vigor. Deep planting had high significant different on the all of parameters. There were no significant different on interaction between germination medium and deep planting on all of observed parameters.